Financial budgets [ (Accounting for small business series, 2001)
By examining the funky clothing and music store euphemism, this program looks at the fundamental issues of financial budgets including why business have budgets, the importance of budgets, the budgeting process, the length of a budget period and planning and evaluation of budgets. With revealing insights from the owner and her staff, see how budgeting plays a critical role in the week-to-week survival of this small business